Philosophy of education concerns purposes, content and methods of education : Philosophy of Education Society of the Philippines seventh yearbook - Botor, Celeste Ordas; Ortinero, Aniceta M. (Rex Book Store, 1994)
Purpose: "They express more fully the education that is more fully the educational ideas in our constitution. The articles aims on, subject matter, methods, and the problems areas most disturbed in education never go stale because they are tested in a new light depending on the unique situations encountered."